Inefficiencies in the Online Sports Betting Markets, and the Role of Varying Margins. An Empirical Study Regarding the European Football Betting Scene. - Baird, David (2022)
The efficiency concept is key when studying financial markets. As many academics have done in the past, this dissertation utilises the sports betting markets as a simple financial market to investigate market efficiency. Using a dataset of 22,294 European football matches, his study implements several empirical models to test the weak form and semi-strong form efficient market hypotheses. Evidence is found to support the presence of a favourite-longshot bias as well as numerous arbitrage opportunities, suggesting deviations from the efficiency hypotheses. This paper is the first to investigate the role that margins play to this extent, finding that they are key in the pursuit of betting market efficiency. This finding highlights the control that bookmakers have on this market, uncovering the consequential limitations when usings betting markets to make inferences on the wider financial markets.